Resultados obtidos com a aplicação da polivalência da mão de obra na construção civil: revisão sistemática - Cardoso, Gabriel Camargo; Abreu, João Paulo Maciel de; Marchiori, Fernanda Fernandes (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Despite its relevance, the construction industry has been facing the same problems for decades. The lack of skilled labour, workers with few opportunities for professional growth, recurrent delays and high turnover rates are sector’s well known and hard to solve problems. Although important in the context of lean thinking, the concept of multi-skill faces resistance due to the learning effect and uncertanties about productivity. Considering the aforementioned situation, this review aims to compile the main results of studies carried out on the effects of multi-skill, when applied to the civil construction reality, as well as to analyse parameters related to the papers in question. A total of twenty-three publications were found in a systematic bibliometric review. Results are partial and are part of a bigger research effort. It was observed that a multifunctional workforce benefits both employees and employers. A shortage of studies with real work environment results was discovered, with most of the papers focusing on computer models.